SISTEM PENDIDIKAN DI NEGARA IRAN - Abdul Wahab Syakharani; Ahmad Rafi’i; Anif Ramadhani; Dilah Dilah; Khairul Muhsinin (CV. ADIBA AISHA AMIRA, 2022)
The Islamic Republic of Iran (or Persia) is a Middle Eastern country located in Southwest Asia. Iran is one of the founding members of the United Nations (UN), Organization of the Islamic Conference (OIC), and the Non-Aligned Movement. The political system in Iran is based on a constitution called the